As contribuições da Psicologia para o Programa Saúde na Escola: uma revisão da literatura - Costa, Klíssia Araújo da (Brasil, 2024)
The process of establishing the Unified Health System (SUS) in Brazil was marked by democratic movements during the 1970s, particularly the health reform, and was significantly influenced by the Federal Constitution of 1988. Psychology has gradually gained a place within this health system, notably through Ordinance No. 154/2008, which facilitated the creation of Family Health Support Centers (NASF) and the inclusion of mental health professionals in primary health care. This development led to the formation of the School Health Program (PSE), aimed at integrating the education and health sectors while promoting access to quality health care for all. The objective of this study is to analyze the contributions of psychology within the context of primary health care and its role in the School Health Program (PSE) through a narrative literature review based on Thematic Analysis (TA). A total of 11 academic studies were examined, including four qualitative and descriptive research projects, a case study, a master's thesis, a course completion work, and four experience reports. Ultimately, the analysis revealed inconsistencies between the guidelines of the PSE and the role of psychologists in the basic health network. Despite psychology making progress within the health sector over the years, it continues to encounter numerous challenges, particularly regarding health promotion and prevention.